Analisis Pengalaman Pengguna Website E-Learning Menggunakan Usability Testing dan User Experience Questionnaire: Analysis of E-Learning Website User Experience Using Usability Testing and User Experience Questionnaire - Irhamullah Irhamullah (WITECH: Jurnal Teknologi Rekayasa Komputer dan Jaringan, 2025)
Digital technology has had a transformational impact on various fields, including education, through the implementation of E-learning. In the context of education, E-learning plays an important role in supporting a flexible and effective learning process. However, optimizing the use of E-learning still faces challenges, one of which is the level of user satisfaction. This factor is crucial, as a good user experience can improve the effectiveness of learning as well as user engagement. This study aims to evaluate the user experience of the E-learning website Hasdemy.com through the usability testing and user experience questionnaire (UEQ) approach. This methodology is designed to provide insights to developers and management to improve the quality of the platform. The results of this study are that the highest average score of the UEQ questionnaire scale on the E-learning website Hasdemy.com is the Dependability scale with an average value of 0.415, then Attractiveness of -0.060, Perspicuity scale of -0.090, Stimulation scale of -0.125, Novelty scale of -0.190, and Efficiency scale of -0.255. The results of the usability testing using the SUS method were obtained with a result of 47.60 for the average score on the SUS score of the E-learning website Hasdemy.com. Overall, it can be concluded that the condition of the E-Learning website Hasdemy.com be in the Percentile Range of 40-50 with a grade of D-, then has the Adjective OK, Acceptable marginal, and passive NPS. Therefore, E-learning websites Hasdemy.com need various improvements to improve the quality of the website from the user's perspective. This research makes an important contribution to the development of more effective, relevant, and user-centered E-learning in the era of digital transformation of education.